170P Anti-α gal antibodies in the context of blood group and stool and tumour-adjacent microbiome in colorectal cancer patients. (15th December 2019) - Selingerova, I; Budinska, E; Zwinsova, B; Mazalova, B; Bencsikova, B; Valik, D; Dubska, L Zdrazilova
Abstract: Background: Gut microbiome plays a role in the development and clinical course of colorectal cancer (CRC). Natural antibodies against galactose-α-1, 3-galactose (α-gal) are highly abundant in humans due to regular stimulation from gut bacteria. Similarly, Abs against AB0 blood group antigens are produced as cross-reacting with intestinal bacteria and α-gal epitope has similar structure to blood group B Ag. Blood group antigens may be associated with an expansion families of gut bacteria. Methods: CRC patients (n = 114) were sampled for stool, tumour tissue swab and blood prior to anti-cancer pharmacotherapy. The level of anti-α-gal Ig was quantified by ELISA in CRC patients and age-matched healthy subjects. 16S rDNA sequencing was analyzed on genus level and data were treated as composition and normalized using centered log-ratio transformation. Anti- α-gal Ig and microbiome composition was tested using linear model and differences between blood groups using ANOVA and post-hoc Tukey HSD test. Results: 1/ The level of anti-α-gal IgA, but not IgG or IgM, is higher in colorectal cancer patients compared to healthy individuals. 2/ There was no association between CRC stage and anti-α-gal Abs level. 3/ The level of anti-α-gal IgG and IgM is lower in CRC patients with blood group B Ag. 4/ The level of anti-α-gal IgG is positively associated with abundance of Tyzzerella and negatively with Eubacterium ruminantium group and Lachnospiraceae UCG-001 in both patient stool and tumour swabs. 5/ The level of anti-α-gal IgA is positively associated with abundance of Collinsella, Barnesiella and Dorea and negatively with Filifactor and Acinetobacter in CRC tumour swabs. 6/ The level of anti-α-gal IgM is positively associated with abundance of Fusicatenibacter and Megamonas and negatively with Lactobacillus and Coprococcus in both stool and tumour swabs. 7/ Prevotella and Victivallis were less and Bacteroides more abundant in tumour swabs from CRC patients with blood group 0. Conclusion: The level of anti-α gal antibodies CRC patients is related with various metabolism influencing bacteria. Blood group antigen B is related to reduced IgM and IgG but not specific microbiome composition. Legal entity responsible for the study: Czech Ministry of Health. Funding: Project AZV 16-31966A (Czech Ministry of Health). Disclosure: All authors have declared no conflicts of interest.